Distribution of Microplastics in Sediments of The Northern Natuna Sea - Dodi Fanhalen Siregar; Agus Saleh Atmadipoera; Ario Damar; Yulianto Suteja; Nabil (Faculty of Fisheries and Marine Universitas Airlangga, 2026)
Graphical Abstract Highlight Research 1. A total of 258 MP in the sediments of the Northern Natuna Sea were identified from eight observation stations with abundances ranging from 400 to 1020 pieces/kg (average 645 ± 199.64 pieces/kg) (dry weight: dw). 2. Fiber and fragment MP were the most commonly found (58% and 40%, respectively), followed by pellets (2%). 3. In terms of color, transparent MP were the most abundant (48%), followed by black (27%), orange (14%), blue (8%), turquoise green (2%), and white (1%). 4. MP in the Northern Natuna Sea range in size from 70 to 6400 μm with an average size of 845.31 μm, where the most abundant size is found in the 500 – 1000 µm range (30%), followed by sizes > 1000 µm (26%); while sizes of 300 – 500 µm and < 300 µm were each found at 22%. 5. MP fibers based on depth show an increase in percentage with increasing depth in the Northern Natuna Sea. 6. The average size of MP decreases with increasing depth in the Northern Natuna Sea, where at a depth of < 110 m the average reaches 1156.57 µm, at a depth of 110 – 120 m it reaches 830.17 µm at a depth of 120 – 130 m, and 754.77 µm at a depth of > 130 m. 7. The diversity of MP types in the sediments of the Northern Natuna Sea according to observation stations shows that Station 1 is the location with the highest number of MP types (4 types: 7 fragment particles, 29 fiber particles, 1 foam particle, and 2 pellet particles); then according to depth, the highest number of MP types was found at a depth of 110 – 120 m (4 types: 13 fragment particles, 43 fiber particles, 1 foam particle, and 2 pellet particles). 8. The diversity of MP sizes according to observation stations showed that the highest number of sizes < 300 µm was found at Station 2 (13 particles) and the highest number of sizes > 1000 µm was found at Station 4 (13 particles); then according to depth, the highest number of sizes < 300 µm and > 1000 µm was found at a depth > 130 m (21 particles each). 9. The diversity of MP colors according to observation stations showed that the highest number of colors was found at Station 2 (7 colors: white 2 particles, black 13 particles, green 1 particle, blue 3 particles, orange 6 particles, turquoise 1 particle, and transparent 25 particles); while according to depth, the highest number of colors was found at a depth of 120 – 130 m (6 colors: white 2 particles, black 21 particles, green 1 particle, blue 5 particles, orange 7 particles, turquoise green 1 particle, and transparent 35 particles). Abstract Many studies on microplastics have been conducted by experts. However, little is known about microplastics in the sediments of the Northern Natuna Sea. For a comprehensive understanding of global microplastic pollution, the quantity of microplastics in the sediments of the North Natuna Sea is crucial to study. This study was conducted at 8 stations with the aim of determining the presence of microplastics in sediments in the Northern Natuna Sea. A total of 50 gr of sediment samples that had been dried, homogenized, and sieved were subjected to density separation and then allowed to settle for 12 hours, after which the microplastics floated and were collected using a vacuum pump or filter paper. Sediment samples were analyzed for microplastic abundance, type, size, and color distribution using ANOVA, Spearman's correlation, cluster analysis, non-metric Multidimensional Scaling (nMDS), and PERMANOVA. The average microplastic abundance was found to be 645 ± 199.64 pieces/kg and the diversity index was classified as high, with no significant difference in the diversity index between depths, indicating diversity in microplastics and that their input also came from many sources. At a depth of 110 – 120 m, fiber microplastics were found to be very high; then at a depth of > 130 m, microplastics measuring < 300 and > 1000 µm were found to be very high; while at a depth of 120 – 130 m, a high number of colored microplastics were found. Microplastic distribution in the North Natuna Sea is primarily influenced by human activities, with their abundance showing a strong correlation with the distance from the coastline. Microplastic size decreases with increasing depth, while microplastic fibers increase with increasing depth. This study found that complex sources of microplastics have polluted the Northern Natuna Sea, with human activity being the biggest influence, thus requiring serious attention.